Governance of mangrove restoration and conservation to climate change resilience in Bintan Island. Issue 1 (July 2021) - Akbar, D; Mariani; Yudiatmaja, W E; Edison
Abstract: Policy of climate change mitigation and adaptation play an important role to socio-economic aspect. Controlling pollution and degradation of environment in coastal area adapted by capacity initiatives to protect marine environment from pollution and climate change. Climate change distributes micro-plastic to the ocean, including the activity of marine debris, fisheries and marine products industry, and shipping line (oil spill). Industry, agriculture in daily life contributes 80% of marine pollution, in addition, hundreds hectares of mangrove deforestation in Kepulauan Riau caused by development. According to Governmental Law No 19 year 1999 of pollution and damage control of the sea and implementation of The Bali Declaration as an adaptation of the 4 th Intergovernmental Review Meeting (IGK4) to the Regional Capacity Canter for Clean Seas (RC3S) in Bali by mainstreaming protection of ocean and coastal ecosystem from the threat of chemical, waste, and micro plastic pollution. Mangrove as one of the best alternative of climate change mitigation divided into several zones, namely zone of core, zone utility and zone sustainability. The goals of this research are mapping the destruction factors and rehabilitation efforts, and also to know the interconnected key stakeholders on conserve mangrove and community based ecological mangrove restoration. Restoration and conservation of Mangrove in Kepulauan Riau, especially in Bintan and Batam, to the management of sustainable coastal through the method of Mangrove Restoration Opportunity Evaluation in collaboration between regional government, private sector, civil society, and expert. In recommendation, according to the program of Agency of Peat and Mangrove Restoration (BRGM) of Presidential Decree No 120/2020 by planting, survey, utility and other researches, mangrove sustainability needs consideration of the legality area and common analysis of Ministry and Provincial Government to avoid misunderstanding of taking action between conserve and build, and also taking further action of RZWP3K in Kepulauan Riau.